The Dynamics of Return Migration, Human Capital Accumulation, and Wage Assimilation - Jérôme Adda; Christian Dustmann; Joseph-Simon Görlach (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This paper develops and estimates a dynamic model where individuals differ in ability and location preference to evaluate the mechanisms that affect the evolution of immigrants' careers in conjunction with their re-migration plans. Our analysis highlights a novel form of selective return migration where those who plan to stay longer invest more into skill acquisition, with important implications for the assessment of immigrants' career paths and the estimation of their earnings profiles. Our study also explains the willingness of immigrants to accept jobs at wages that seem unacceptable to natives. Finally, our model provides important insight for the design of migration policies, showing that policies which initially restrict residence or condition residence on achievement shape not only immigrants' career profiles through their impact on human capital investment but also determine the selection of arrivals and leavers.
Keywords: F22; J24; J61; 330; international migration; human capital; expectations